Unravelling spinal circuits of pain and mechanical allodynia - Gangadharan, Vijayan; Kuner, Rohini (Neuron, 2015)
How do spinal circuits mediating tactile sensation and pain get entangled to evoke allodynia, i.e., pain sensation, in response to a normally innocuous stimulus? Recent breakthroughs are now closing this long-standing, critical gap. VGLUT3-expressing neurons and their polysynaptic connectivity to calretinin-expressing neurons are now identified as key determinants of the spinal circuitry underlying mechanical allodynia.
Gesehen am 10.07.2020